2022
DOI: 10.3390/ijms231810957
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Venetoclax-Based Treatments in Acute Lymphoblastic Leukemia

Abstract: Venetoclax, a B-cell lymphoma (BCL-2) inhibitor, in combination with hypomethylating agents has become the new standard of care in elderly and unfit patients with acute myeloid leukemia, with significantly improved overall survival and quality of life. Studies of venetoclax combined with high-dose chemotherapy are emerging with evidence of higher rates of molecular remission. Recently, a growing number of publications bring forth the use of venetoclax in patients with acute lymphoblastic leukemia (ALL). In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Nonetheless, in most cases treatment was considered as a bridge to an allogeneic bone marrow transplant. Among the ven‐chemotherapy regimen, we report a CR/CRi rate of 55%, which is similar to previous reports in the r/r setting 4 . In the ven‐navitoclax‐based chemotherapy cohort, we report a similar ORR, but lower CR/CRi rate of 25%.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Nonetheless, in most cases treatment was considered as a bridge to an allogeneic bone marrow transplant. Among the ven‐chemotherapy regimen, we report a CR/CRi rate of 55%, which is similar to previous reports in the r/r setting 4 . In the ven‐navitoclax‐based chemotherapy cohort, we report a similar ORR, but lower CR/CRi rate of 25%.…”
Section: Discussionsupporting
confidence: 88%
“…Among the ven-chemotherapy regimen, we report a CR/CRi rate of 55%, which is similar to previous reports in the r/r setting. 4 In the ven-navitoclax-based chemotherapy cohort, we report a similar ORR, but lower CR/CRi rate of 25%. None of the patients with previous exposure to venetoclax achieved CR.…”
Section: Safety and Toxicitysupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, it has been universally reported that the PI3K-AKT signaling pathway is hyperactive in ALL, promoting the survival of leukemic stem cells as well as the development of the leukemic bone marrow microenvironment and drug resistance (33)(34)(35). In addition, studies have confirmed that dysregulated expression of apoptosis TFs can promote the incidence of leukemia, and the overexpression of BCL2 is associated with leukemia drug resistance (36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 95%
“…Given the encouraging results in adult populations, venetoclax holds the potential for promising results in pediatric patients as well. A phase I/II multicenter study (NCT04029688) is assessing the murine double minute 2 homolog (MDM2) inhibitor idasanutlin combined with chemotherapy or venetoclax in pediatric and young adult patients with r/r acute leukemias or solid tumors (61,62). Similarly, an additional phase I study is evaluating venetoclax in combination with CPX-351 in children, adolescents, and young adults with acute r/r leukemias (63).…”
Section: B Cell Leukemia/lymphoma-2 (Bcl-2) and Bcl-x L Inhibitorsmentioning
confidence: 99%